Employees competences-the success factor of commerce enterprises - Cristinel Vasiliu (Amfiteatru Economic Journal, 2009)
Researches done in different areas of economic field have revealed that behind the performance of enterprises we find people. This truth is also valid for the commercial area. The commerce enterprise has some characteristic features among which there are: lack of common tools of other types of organisation for measurement of managerial performances, less degree of mechanisation and automation of activities, discontinuity of activities in work program caused by clients absence, the increased personnel expenses as part of the total expenses, significant seasonality impact, which can be manifested either in the activity period (the open season for example), or in consuming, or as a consequence of production seasonality, relatively increased number of clients to whom they address - very much in case of retail enterprises and quite much of those of wholesaling -, selling of a great number of products - the commerce firms who sell one or a few articles being exceptionally cases etc. All of these raise the problem of competences, abilities and necessary knowledge for a propey performance of commerce enterprise activities with the goal to reach their profitability. Therefore, as a succession of an exploratory research I have defined a commercial specialist profile, based on o few general and specific competences. Starting from these competences, curricula of preparing institutions can be designed with the goal of adapting these to business area requirements.
Keywords: I23; M53; O15; 330; competence; ability; knowledge; learning; preparation